Towards Sustainable Livelihood of the Population. The Contributions of Health and Educational Institutions: A comparative Study of UK and Ghana - Gokah, Amen Kofi (My University, 2012)
It is the aim of every government to see to the welfare of its citizens to attain certain level of livelihood which is deemed sustainable with the exception of some few countries where tyranny rules. And the government amasses wealth to satifify therir selfish desires. Welfare state can be defined as: “A system in which the government undertakes the chief responsibility for providing for the social and economic security of its population, usually through unemployment insurance, old age pensions, and other socialsecurity measures; A social system characterized by such policies”. (Collins English Dictionary 2000) A livelihood is sustainable when it can cope with and recover from stresses and shocks and maintain or enhance its capabilities and assets both now and in the future (DFID 2000). This requires efforts on the parts of the government to provide welfare services to the population and the population contributing their quota through their own efforts as well to attain a livelihood which is sustainable. The main aim of this paper is to find out how education and health service provisions helps people to attain sustainable livelihoods in United Kingdom and Ghana. In so doing the role of the government in welfare provision were looked at but due to various limitations the paper dwelt much on only education and health as welfare services. Also, some theories of welfare States, information about the educational and health system in the United Kingdom and Ghana were looked at. The paper uses qualitative approach by analysing secondary data due to time and financial limitations. The results presented in this paper was done by critically looking at the data and drawing conclusions from it. It was found out among other things that even though United Kingdom is a developed country by all standard, Ghana is a developing country and is historically linked to United Kingdom through Colonialism and still does so through the Commonwealth of Nations thereby making comparisons between the two countries possible. Also comparison between the two countries was possible because the paper looked at what is happening at two geographical locations (Continents in this case Africa and Europe which defined the geographical scope of the research) and also the situation in a developed country and a developing country. Since the paper considers only health and education provisions as welfare services which is a basic limitation of this paper but also the strength because education and health sectors are the two giant sectors in welfare states. It implies that future researchers can look at other aspects of welfare services like social care among others. There are therefore possibilities for future research and readers of this paper are therefore advised to narrow their scope to health and education in the assessment and criticisms that may bother their minds.
Keywords: Sustainable Livelihood; Welfare States; Education; Health; Ghana; United Kingdom; Welfare Provision; Welfare Services; Sustainable Livelihood Framework.; fi=Julkisjohtaminen: julkisjohtamisen ohjelma|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|